Regulasi Dan Strategi Kebijakan Pengelolaan Dana Bergulir: Analisis Problematika dalam Implementasinya di Kabupaten Bangka Tengah - Wirazilmustaan; Rahmat Robuwan (Jurnal Risalah Hukum, 2019)
Economic democracy gives the state an active role in building a national-based national economic synergy that is gathered in the nuances of nationalism. One of the implementations of Indonesia's economic development in knitting the people's economy is the Revolving Fund Program. This program is not only a manifesto of central government, but it is also being implemented at the regional level. This is in consistent with the principle of Indonesia's decentralization. One of the regional governments that has implemented a revolving fund is the Regional Government of Central Bangka Regency since 2011 on te basis of local regulations. The revolving fund management program in Central Bangka Regency has a problem. Especially regarding the regulatory arrangements that form the legal basis. Therefore, a revision of the Regional Regulation regarding the management of revolving funds is needed. The implementation of the Revolving Fund Program as a program to develop the progress of Cooperatives and Micro, Small and Medium Enterprises in Central Bangka is an effective breakthrough. But until now, revolving funds have only been given to micro, small and medium businesses, while cooperatives in Central Bangka Regency have not been able to use revolving funds to increase their business capacity.